Complex Leadership in Healthcare: A Scoping Review - Zakaria Belrhiti; Ariadna Nebot Geralt; Bruno Marchal (Kerman University of Medical Sciences, 2018)
Background Nowadays, health systems are generally acknowledged to be complex social systems. Consequently, scholars, academics, practitioners, and policy-makers are exploring how to adopt a complexity perspective in health policy and system research. While leadership and complexity has been studied extensively outside health, the implications of complexity theories for the study of leadership in healthcare have received limited attention. We carried out a scoping review of complex leadership (CL) in healthcare to investigate how CL in healthcare has been defined, theorised and conceptualised and to explore how 'CL' has been applied in healthcare settings. Methods We followed the methodological steps proposed by (Arksey and O'Malley, 2005): (1) specifying the research question, (2) identifying relevant studies, (3) study selection, (4) charting the data, (5) collating and summarizing the findings, and (6) reporting the results. We searched using Medline, Psychinfo, Wiley online library, and Google Scholar. Our inclusion criteria were: publication type (peer reviewed articles, theses, and book chapters); phenomenon of interest: complex leadership; context: healthcare and period of publication: between 2000 and 2016. Results Our search and selection resulted in 37 papers (16 conceptual papers, 14 empirical studies and 7 advocacy papers). We note that empirical studies on CL are few and almost all research reported by these papers was carried out in the North (mainly in USA and UK). We found that there is some variation in definitions of CL. Furthermore, the research papers adopt mostly an explorative or explanatory approach and do not focus on assessing effectiveness of CL approaches. Finally, we found that the majority of researchers seem to adhere to the mathematical complexity perspective. Conclusion Complexity concepts derived from natural sciences may not automatically fit management of health services. Further research into how social complexity theories may offer researchers useful grounds to empirically test CL theories in health settings is warranted. Specific attention should be paid to the multi-layered nature of leadership.